DIAGNOSTIC ACCURACY OF ULTRASOUND IN DETECTING MENISCAL TEARS TAKING MAGNETIC RESONANCE IMAGING AS GOLD STANDARD - Omer, MA; Malik, SS; MALIK, AA; Anjum, MN; Riaz, Az; Ali, R (Biological and Clinical Sciences Research Journal, 2020)
Meniscal tears are mostly seen worldwide. Multiple imaging modalities are currently used to evaluate pathologic conditions of the knee. MRI can be referred as the non-invasive gold standard investigation to help establishing diagnosis of meniscal tears, but it economically unaffordable to most of patients and needs long examination times. Ultrasound is a possible alternative to MRI. It is simple, convenient and an inexpensive and non-invasive method. The use of ultrasound in identifying meniscal tears has been proposed, but its diagnostic accuracy remains controversial. The objective of the research is to define the diagnostic accurateness of ultrasound scan in detecting meniscal tears taking magnetic resonance imaging as gold standard. It was a diagnostic cross-sectional study in which 78 patients visiting Department of Diagnostic Radiology, Doctors Hospital, Lahore were included. Convenient sampling technique was used. Written informed consent was taken from all the patients. Patients were investigated with the help of ultrasound and results were noted on the designed proforma, subsequently the results were compared to the MRI scan of the knee joint. Data was entered and statistically analyzed using SPSS 21.0. Frequency tables were generated for all variables. For quantitative data like age mean and standard deviation were calculated and for qualitative data like sex and meniscal tears percentages were calculated. Sensitivity, Specificity, Positive Predictive Value, Negative Predictive Value was given. Bar and pie charts were used to present categorical data. Kappa analysis was utilized. The mean age of the patients was 38.18+12.818 years, 82.1% were males and 47.4% had sports trauma. Out of 48 medial meniscus tear on USG, 38(48.7%) were true positive and 10(12.8%) were false positive on MRI. Out of 10 lateral meniscus tear on USG, 9(11.5%) were true positive and 1(1.3%) was false positive on MRI. The sensitivity, specificity, PPV, NPV and diagnostic accuracy of ultrasound for medial meniscus tears were 95.00%, 73.68%, 79.16%, 93.33% and 84.61% while for lateral meniscus tears were 75.00%, 98.48%, 90.00%, 95.58% and 94.87%, respectively. Study concluded that ultrasound has good diagnostic accuracy when compared with magnetic resonance imaging in detecting meniscal tears.